2014
DOI: 10.1128/aac.02438-14
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Cefuroxime in Porcine Cortical and Cancellous Bone Determined by Microdialysis

Abstract: f Traditionally, the pharmacokinetics of antimicrobials in bone have been investigated using bone biopsy specimens, but this approach suffers from considerable methodological limitations. Consequently, new methods are needed. The objectives of this study were to assess the feasibility of microdialysis (MD) for measuring cefuroxime in bone and to obtain pharmacokinetic profiles for the same drug in porcine cortical and cancellous bone. The measurements were conducted in bone wax sealed and unsealed drill holes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…In agreement with our previous study, the poorest tissue penetration was found for bone (15). Somewhat surprisingly, bone penetration in the CI group was poorer than in the STI group, but this seems partly compensated for by higher free plasma AUCs.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In agreement with our previous study, the poorest tissue penetration was found for bone (15). Somewhat surprisingly, bone penetration in the CI group was poorer than in the STI group, but this seems partly compensated for by higher free plasma AUCs.…”
Section: Discussionsupporting
confidence: 79%
“…In a recent porcine study, we demonstrated substantially impaired bone and subcutaneous tissue (SCT) penetration of cefuroxime (15). The pharmacokinetic profiles suggested that EI or CI of the drug might attain increased time with tissue concentrations above the MIC (TϾMIC) for relevant microorganisms.…”
mentioning
confidence: 99%
“…Cortical bone tissue has a higher Young's modulus compared with trabecular bone tissue, and the higher degree of mineralization of cortical bone contributes to a stiffer, but more brittle tissue compared with single trabeculae . In addition, cortical bone and trabecular bone show different metabolic behaviors in many physiological and pathological processes, such as glycation, pharmacokinetics, and their response to diet and implant insertion . The difference in metabolic activity is best demonstrated by their different remodeling process, which has significant clinical relevance for the treatment of osteoporosis .…”
mentioning
confidence: 99%
“…Due to this structure, cancellous bone has a bigger contact surface area with vascularization and bone marrow compared to trabecular bone, which makes it more suitable for drug‐to‐bone interaction. This bigger contact surface explains the higher drug concentration found in the epiphysis compared to the diaphysis . The exact mechanism of how drugs are incorporated in skeletal tissue is still under discussion.…”
Section: Introductionmentioning
confidence: 99%
“…This bigger contact surface explains the higher drug concentration found in the epiphysis compared to the diaphysis. 7 The exact mechanism of how drugs are incorporated in skeletal tissue is still under discussion. A recent model gives a possible explanation for the incorporation of drugs into bone tissue.…”
Section: Introductionmentioning
confidence: 99%